Penerapan Kreativitas Melalui Eksprimen dan Musik dalam Pengembangan Kemampuan Kognitif Anak Usia Dini - Nasution, Nur Kholidah (SYAMIL: Journal of Islamic Education, 2017)
This research attempts to (1) describe the development of creativity through experiment, (2) and give some stimulation for childrens to try and explore their experiences (3) for developing the creativity of the children's be means of experiments (4) developing music creativities (5) Music for early childhood developments. The early childhood it's being primary ages and has characterized to discover something. Childrens exactly more interest for studying with practice directly than just hearing and seeing around .children are very happy to learn by dealing directly with material presented. A good example for this is when children were taken out of the room and for developing their capabilities with experiment greatly helping children to be more creatives and intelligence. The importance of music for early childhood attempting to increase their creativities and imagination and able to stimulate the memory. Therefore music is very useful o teach children for better development. Music is a place to express the atmosphere of self because with music childrens given opportunity to express their feelings and ideas by dancing and moving by following music sounds